LEMBAGA PEMASARAN IKAN TERI KERING (Stolephorus indicus) DI DESA TANJUNG LALAK KECAMATAN PULAU LAUT KEPULAUAN KABUPATEN KOTABARU PROVINSI KALIMANTAN SELATAN - Emmy Lilimantik; Karmila Sari (EnviroScienteae, 2022)
This research aims to determine the marketing institution of dried anchovy in Tanjung Lalak Village, Pulau Laut Sub-District, Kotabaru Regency, South Kalimantan Province. The data used are primary data and secondary data, while the data collection technique used are survey, interview and documentation methods. The research location was determined using a purposive sampling method, the sampling method of respondents used is the Simple Random Sampling and the Snowball Sampling method is used for the sample of traders. The data analysis used is (1) marketing channel analysis and (2) marketing agency analysis. The results of the analysis show that (1) marketing channels consist of 3 patterns of marketing channels, which are (a) Producers, Retailers and Final Consumers, (b) Producers, Collecting Traders, Retailers and Final Consumers and (c) Producers, Retailers, Agents Outside the city and (2) there are three marketing institutions involved in the marketing of anchovy in Tanjung Lalak village, namely collectors, retailers and inter-regional traders.